Internationalization and Regional Entrepreneurship in China - Elston,Julie; Weidinger,Alois (Small Business Economics, 2019)
This study examines the importance of geographic location on the empirical link between internationalization and entrepreneurial intention. Integrating data from multiple sources to create a measure of internationalization intensity, this study directly contributes to the literature by revealing a significant and more complex relationship between internationalization and entrepreneurship than previously suggested in the literature. Specifically, while highly internationalized locations allow better access to resource markets they may also hinder entrepreneurship for several reasons, including the fact that these locations have higher competition for resources. Results provide direct empirical support to recent theories on the importance of within country comparative differences.
Keywords: Accounting; Finance; OSU-Cascades